Changing scenario of postgraduate medical education in Nepal - Nepal, B P (Kathmandu University Medical Journal, 2012)
No abstract available. DOI: http://dx.doi.org/10.3126/kumj.v8i3.6213 Kathmandu Univ Med J 2010;8(3):290-91